Photoinduced Jahn–Teller switch in Mn(iii) terpyridine complexes. Issue 28 (18th May 2022) - Barlow, Kyle; Eng, Julien; Ivalo, Iona; Coletta, Marco; Brechin, Euan K.; Penfold, Thomas J.; Johansson, J. Olof
Abstract : Ultrafast transient absorption spectra were recorded for [Mn(terpy)X3 ], where X = Cl, F, and N3, to explore photoinduced switching from axial to equatorial Jahn–Teller (JT) distortion. Abstract : Ultrafast transient absorption spectra were recorded for [Mn(terpy)X3 ], where X = Cl, F, and N3, to explore photoinduced switching from axial to equatorial Jahn–Teller (JT) distortion. Strong oscillations were observed in the transients, corresponding to a wavepacket on the excited-state potential energy surface with oscillation frequency around 115 cm −1 for all three complexes. Multireference quantum chemistry calculations indicate that the reaction coordinate is a pincer-like motion of the terpyridine ligand arising from bond length changes in the excited state due to the JT switch. We observed long dephasing times of the wavepacket, with times of 620 fs for [Mn(terpy)Cl3 ], 450 fs for [Mn(terpy)F3 ], and 370 fs for [Mn(terpy)(N3 )3 ]. The dephasing time of these coherences decreases with an increasing number of vibrational modes at lower energy than the mode dominating the reaction coordinate, suggesting they act as an effective bath to dissipate the excess energy obtained from photoexcitation.